Learning and Faith: On calling papyri ‘school texts’ and ‘Christian’ - Mugridge, Alan (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
This article is a review of those papyri, including wooden tablets and ostraca, which are listed as (certainly or possibly) ‘school texts’ on LDAB, whose religious orientation is given as ‘Christian,’ and which may have been written up to the end of IVAD. It is concluded that some papyri should not be considered here, since they cannot be classed primarily as school texts, their dating is too late, there is no reason to call them ‘Christian,’ or there is little known about them – although, as a whole, the Christian school texts deserve special consideration in the palaeography of early Christian papyri. It is also shown, however, that some of these papyri have only a tenuous connection with Christian faith, since they only include words that belong to ‘a Christian milieu,’ while others have a much stronger claim to be called Christian because they contain parts of known Christian works. The designation of this group of papyri as both ‘school texts’ and ‘Christian’ is no simple matter; and some implications of this are drawn, especially with regard to using some of these papyri in the textual criticism of the Greek OT, as well as the NT.